Swimming Coached–Management Program of Indonesian Swimming Association in South Sumatera (Journal of Physical Education and Sports, 2018)
The research objectives are to evaluate and to analyze: (1) the antecedent covering background and objective of coaching program at Indonesian Swimming Association or PRSI (Persatuan Renang Seluruh Indonesia) in South Sumatera; (2) the transaction including athletes and trainers recruitment, implementation of training programs, facilities and infrastructures, consumption, coordination, transportation, welfare of trainers and athletes, funding sources of coaching programs of PRSI in South Sumatera; (3) the outcome encompassing the success of swimming program of PRSI in South Sumatera. Then, this research used qualitative research by applying evaluation of Countenance (Stake). From this research, it can be concluded that; (1) the antecedent of both the background and the purpose of coaching program are clear, (2) the transaction of the recruitment system of both trainers and athletes and the implementation of the training have done well, the national and international standard facilities and infrastructures have been proper maintained, the availability of consumption of athletes is in poor conditions, the transportation used by athletes and coaches is quite good, the coordination and the funding obtained are run well; (3) the outcome of coaching program at PRSI of South Sumatera has decreased.